Prognostic Value of Elevated Cardiac Troponin I After Aneurysmal Subarachnoid Hemorrhage - Lin, Fa; Chen, Yu; He, Qiheng; Zeng, Chaofan; Zhang, Chaoqi; Chen, Xiaolin; Zhao, Yuanli; Wang, Shuo; Zhao, Jizong (Frontiers in Neurology, 2021)
Object: Patients with aneurysmal subarachnoid hemorrhage (aSAH) have an increased incidence of cardiac events and short-term unfavorable neurological outcomes during the acute phase of bleeding. We studied whether troponin I elevation after ictus can predict future major adverse cardiac events (MACEs) and long-term neurological outcomes after two years. Methods: Consecutive aSAH patients within three days of bleeding were eligible for review from a prospective observational cohort (ClinicalTrials.gov Identifier: NCT04785976). Potential predictors of future MACEs and unfavorable long-term neurological outcomes were calculated by Cox and logistic regression analyses. Additional Kaplan-Meier curves were performed. Results: A total of 213 patients were enrolled with an average follow-up duration of 34.3 months. Individuals were divided into two groups, elevated cTnI group and unelevated cTnI group. Until the last available follow-up, 20 patients had died, with an overall all-cause mortality rate of 9.4% and an annual all-cause mortality rate of 3.8%. Patients with elevated cTnI had a significantly higher risk of future MACEs (10.6% vs 2.1%, p=0.024, 95% CI 1.256-23.875) and unfavorable neurological outcomes at discharge, 3-month, 1-year, 2-year and last follow-up (p=0.001, p<0.001, p=0.001, p<0.001, p<0.001, respectively). In the Cox analysis for future MACE, elevated cTnI was the only independent predictor (HR 5.980; 95% CI 1.428-25.407, p=0.014). In the multivariable logistic analysis for unfavorable neurological outcomes, peak cTnI was significant (OR 2.951; 95%CI 1.376-6.323; p=0.005). Kaplan-Meier analysis indicated that the elevated cTnI was correlated with future MACE (log-rank test, p=0.007) and subsequent death (log-rank test, p=0.004). Conclusion: CTnI elevation after aSAH could powerfully predict future MACEs and unfavorable neurological outcomes.